2022
DOI: 10.1001/jamanetworkopen.2022.30367
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Minocycline on Depressive Symptoms in Patients With Treatment-Resistant Depression

Abstract: IMPORTANCEInsufficient treatment response and resulting chronicity constitute a major problem in depressive disorders. Remission rates range as low as 15% to 40% and treatment-resistant depression (TRD) is associated with low-grade inflammation, suggesting anti-inflammatory interventions as a rational treatment strategy. Minocycline, which inhibits microglial activation, represents a promising repurposing candidate in the treatment of TRD. OBJECTIVE To determine whether 6 weeks of minocycline as add-on to anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 44 publications
1
29
0
1
Order By: Relevance
“…Minocycline crosses the bloodbrain barrier, inhibits proinflammatory activation of microglial cells and is neuroprotective. 8 But in a recent study of 173 people who failed to respond adequately to an initial antidepressant, six weeks add-on treatment with minocycline did not reduce depressive symptoms any more than placebo. 8 "Specialists are prescribing antiinflammatories off-label in combination with other treatments for people with severe depression that doesn't respond well to other inter ventions," says Professor Pariante.…”
Section: Inflammation and Depressionmentioning
confidence: 97%
See 3 more Smart Citations
“…Minocycline crosses the bloodbrain barrier, inhibits proinflammatory activation of microglial cells and is neuroprotective. 8 But in a recent study of 173 people who failed to respond adequately to an initial antidepressant, six weeks add-on treatment with minocycline did not reduce depressive symptoms any more than placebo. 8 "Specialists are prescribing antiinflammatories off-label in combination with other treatments for people with severe depression that doesn't respond well to other inter ventions," says Professor Pariante.…”
Section: Inflammation and Depressionmentioning
confidence: 97%
“…8 But in a recent study of 173 people who failed to respond adequately to an initial antidepressant, six weeks add-on treatment with minocycline did not reduce depressive symptoms any more than placebo. 8 "Specialists are prescribing antiinflammatories off-label in combination with other treatments for people with severe depression that doesn't respond well to other inter ventions," says Professor Pariante. "Current anti-inflammatories carry a risk of side-effects, such as gastrointestinal bleeding with NSAIDs.…”
Section: Inflammation and Depressionmentioning
confidence: 97%
See 2 more Smart Citations
“…These results highlight possible sex differences in the neuroprotective and anti-depressant effects of minocycline, with male-sex being possibly associated a better outcome than female-sex. A recent, large clinical trials by Hellmann-Regen et al (2022) found no effects of minocycline on depressive symptoms; although they stratified their sample for median CRP values, these were indicative of very low inflammation, with median values equivalent to approximately 1.2 mg/L in the minocycline arm and 0.6 mg/L in the placebo arm; moreover, they stratified the sample by sex but did not look at sex by CRP groups interaction ( Hellmann-Regen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%